Defective mitochondria‐lysosomal axis enhances the release of extracellular vesicles containing mitochondrial DNA and proteins in Huntington's disease. Issue 10 (14th October 2022) - Beatriz, Margarida; Vilaça, Rita; Anjo, Sandra I.; Manadas, Bruno; Januário, Cristina; Rego, A. Cristina; Lopes, Carla
Abstract: Mitochondrial and autophagy dysfunction are mechanisms proposed to be involved in the pathogenesis of several neurodegenerative diseases. Huntington's disease (HD) is a progressive neurodegenerative disorder associated with mutant Huntingtin‐induced abnormalities in neuronal mitochondrial dynamics and quality control. Former studies suggest that the removal of defective mitochondria may be compromised in HD. Mitochondrial quality control (MQC) is a complex, well‐orchestrated pathway that can be compromised through mitophagy dysregulation or impairment in the mitochondria‐lysosomal axis. Another mitochondrial stress response is the generation of mitochondrial‐derived vesicles that fuse with the endolysosomal system and form multivesicular bodies that are extruded from cells as extracellular vesicles (EVs). In this work, we aimed to study the presence of mitochondrial components in human EVs and the relation to the dysfunction of both mitochondria and the autophagy pathway. We comprehensively characterized the mitochondrial and autophagy alterations in premanifest and manifest HD carriers and performed a proteomic and genomic EVs profile. We observed that manifest HD patients exhibit mitochondrial and autophagy impairment associated with enhanced EVs release. Furthermore, we detected mitochondrial DNA and proteins in EVs released by HD cells and in neuronal‐derived EVs including VDAC‐1 and alpha and beta subunits of ATP synthase F1. HD‐extracellular vesicles transport higher levels of mitochondrial genetic material in manifest HD patients, suggesting an alternative pathway for the secretion of reactive mitochondrial components. This study provides a novel framework connecting EVs enhanced release of mitochondrial components to mitochondrial and lysosomal dysfunction in HD.